Prevalence, awareness, treatment and control of dyslipidaemia and their determinants: results from a population-based survey of 60 283 residents in eastern China - Yijia Chen; Nan Zhou; Xin Hong; Weiwei Wang; Jinling Du; Yingqian Song (BMJ Open)
Objectives To investigate the prevalence, awareness, treatment and control of dyslipidaemia and its associated factors in eastern China.Design Cross-sectional study.Setting Data were collected from the 2017 Nanjing Chronic Disease and Risk Factor Surveillance.Participants This study included 60 283 participants aged ≥18 years.Outcome measures Prevalence of dyslipidaemia was defined as self-reported history of dyslipidaemia and/or the use of lipid-lowering medication, and/or meeting at least one of the following during on-site investigation: total cholesterol ≥6.2 mmol/L, triglyceride ≥2.3 mmol/L, low-density lipoprotein cholesterol ≥4.1 mmol/L and high-density lipoprotein cholesterol <1.0 mmol/L. Dyslipidaemia awareness was defined as the proportion of patients with dyslipidaemia who explicitly indicate their awareness of having a diagnosis of dyslipidaemia. Treatment was based on medication use among individuals with dyslipidaemia. Control was defined as having dyslipidaemia, receiving treatment and achieving serum lipid control to the standard level.Analysis Complex weighting was used to calculate weighted prevalence. A two-level logistic regression model determined the influencing factors for dyslipidaemia prevalence, awareness, treatment and control.Results The crude prevalence rate of dyslipidaemia was 28.4% (17 093 of 60 283). Among 17 093 patients with dyslipidaemia, the crude rates of awareness, treatment and control were 40.0% (n=6830), 27.5% (n=4695) and 21.9% (n=3736), respectively. The corresponding weighted prevalence rates were 29.8%, 41.6%, 28.9% and 22.9%. Older age (OR 2.03, 95% CI 1.82 to 2.23), urban residence (1.24, 1.19 to 1.31), higher education level (1.31, 1.21 to 1.42), current smoking (1.22, 1.15 to 1.29), alcohol consumption (1.20, 1.14 to 1.26), obesity (2.13, 1.99 to 2.29), history of hypertension (1.64, 1.56 to 1.71) and diabetes (1.92, 1.80 to 2.04) were identified as independent risk factors for dyslipidaemia (all p<0.001). Participants who were older, female, living in urban areas, had higher education levels, did not smoke or drink alcohol, had central obesity, had hypertension or had diabetes were more likely to be aware of their dyslipidaemia conditions, receive treatment and achieve serum lipid control to a standard level than their comparators (all p<0.05).Conclusions The prevalence of dyslipidaemia is relatively high in eastern China; however, awareness, treatment and control levels are relatively low.